One magic moment - Kurland, Lynn.; Copyright Paperback Collection Library of Congress (New York, N.Y.: Jove Books, 2011)
Medieval studies scholar Tess Alexander is thrilled for the chance to live in a medieval castle. But then a trip to the village brings her face to face with the owner of the local garage, who looks a great deal like the man who married her sister ... 800 years in the past.
Keywords: Paranormal fiction; Time travel; Man-woman relationships; England; Fantasy fiction; Love stories